2021
DOI: 10.1186/s13098-021-00698-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity amongst GLP-1 RA cardiovascular outcome trials results: can definition of established cardiovascular disease be the missing link?

Abstract: Atherosclerotic cardiovascular diseases are the leading cause of adverse outcomes in patients with type 2 diabetes, and all new anti-diabetic agents are mandated to undergo cardiovascular outcome trials (CVOTs). Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are incretin mimetics that reduce blood glucose levels with a low associated risk of hypoglycaemia. CVOTs with different GLP-1 RAs yielded different results in terms of major cardiovascular composite outcome (MACE), with some trials showing superiori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Although there was a difference in the results obtained across all the trials, some CVOTs provided superiority in the treatment arm, while others only demonstrated non-inferiority ( Table 1 ). 1 …”
Section: Antidiabetic Medications and CV Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there was a difference in the results obtained across all the trials, some CVOTs provided superiority in the treatment arm, while others only demonstrated non-inferiority ( Table 1 ). 1 …”
Section: Antidiabetic Medications and CV Outcomesmentioning
confidence: 99%
“…These results showed that GLP-1RAs are associated with better CV outcomes. 1 Composite CV outcomes from several multicentre, double-blinded, randomised, placebo-controlled trials involving different GLP-1RAs namely lixisenatide, liraglutide, semaglutide, exenatide, albiglutide, dulaglutide and oral semaglutide have demonstrated a non-inferiority in reducing the CV outcomes. Among all of the GLP-1Ras included in an overview, liraglutide, subcutaneous semaglutide, albiglutide and dulaglutide demonstrated a significant reduction in the overall composite CV outcomes.…”
Section: Antidiabetic Medications and CV Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…All agents within this class not only demonstrate significant reductions in HbA1c but also a favourable effect on weight and a lower risk of hypoglycaemia. Treatment with GLP-1 receptor agonists is also recommended as a first option in patients with T2DM at onset, especially in those at risk of cardiovascular disease, due to an important effect on both the primary and secondary prevention of ischemic disease [ 30 ]. In particular, liraglutide, dulaglutide and semaglutide have been shown to reduce major cardiovascular events.…”
Section: Glucagon-like Peptide-1 Receptor Agonists (Glp-1ras)mentioning
confidence: 99%